2015
DOI: 10.1155/2015/878164
|View full text |Cite
|
Sign up to set email alerts
|

Huangqi Jianzhong Tang for Treatment of Chronic Gastritis: A Systematic Review of Randomized Clinical Trials

Abstract: To assess the clinical effects and safety of Huangqi Jianzhong Tang (HQJZ) for the treatment of chronic gastritis (CG), three English databases and four Chinese databases were searched through the inception to January 2015. In randomized controlled trials (RCTs) comparing HQJZ with placebo, no intervention and western medicine were included. A total of 9 RCTs involving 979 participants were identified. The methodological quality of the included trials was generally poor. Meta-analyses demonstrated that HQJZ pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…To be included in the systematic review, the studies had to meet the following criteria: (1) the type of design was RCT; (2) the articles were published in English or Chinese peer-reviewed journals; (3) the trials compared SJZD with standard medical care or inactive intervention(s) for CAG, such as triple therapy or placebo, and combined therapy of SJZD plus conventional therapies compared with conventional therapies alone was also retrieved; (4) outcome measurement used a validated tool. The primary outcome measures included the incidence of gastric cancer and the improvement of atrophy, intestinal metaplasia, and dysplasia based on the gastroscopy and pathology [ 15 ]. Subsequently, we could calculate the overall effect rate according to the improvement of gastroscopy and pathology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be included in the systematic review, the studies had to meet the following criteria: (1) the type of design was RCT; (2) the articles were published in English or Chinese peer-reviewed journals; (3) the trials compared SJZD with standard medical care or inactive intervention(s) for CAG, such as triple therapy or placebo, and combined therapy of SJZD plus conventional therapies compared with conventional therapies alone was also retrieved; (4) outcome measurement used a validated tool. The primary outcome measures included the incidence of gastric cancer and the improvement of atrophy, intestinal metaplasia, and dysplasia based on the gastroscopy and pathology [ 15 ]. Subsequently, we could calculate the overall effect rate according to the improvement of gastroscopy and pathology.…”
Section: Methodsmentioning
confidence: 99%
“…Mucosal-protective agents and proton pump inhibitor were most commonly used medications for chronic gastritis in China [ 13 ]. However, the medications still cannot meet clinical needs with respect to efficacy [ 14 , 15 ]. And patients with long-term western medicine use such as proton pump inhibitor may have a higher possibility of experiencing either diffuse or linear/micronodular enterochromaffin-like cell hyperplasia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ ] Clinical experiments showed that HQJZ was more effective in improving overall gastroscopy outcome than western medicine alone for treatment of chronic gastritis. [ ] The pharmacological experiments with CAG rats also showed that HQJZ could significantly regulate the level of serum gastrin, inhibit the secretion of gastrin and pepsinogen and gastric mucosa acid. [ ] Besides, HQJZ could increase the content of substance gastrointestinal hormone SP (substance P) in gastric antrum and promote gastric emptying.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly used for tonifying qi and dispelling cold, as well as for strengthening the stomach (Zhang, ). Modern pharmacological studies have shown that it is effective in the treatment of gastrointestinal diseases caused by spleen deficiency (Liu, Cui, et al, ; Liu, Jiang, Wang, Wang, & Wu, ; Liu, Xu, Wang, & Qin, ; Wang, ; Wei et al, ). In addition, some studies have shown that HQJZ has sedative and spasmolytic effects, as well as exhibits hypoglycemia‐, blood composition‐, and immune function‐regulating effects (Chen, ; Chen et al, ; Qian, Jiang, Bao, & Wei, ; Su et al, ; Zhang & Yu, ).…”
Section: Introductionmentioning
confidence: 99%